Adequation entrequantite de pate stimulante et production de caoutchouc d'Hevea brasiliensis dans le sud-est de la Cote d'Ivoire - Obouayeba S; Boa D; Keli Z.J. (Tropicultura, 1996)
Summary in English
Keywords: Hevea brasiliensis; Length of tapping cut; Metabolic activity; Productivity; Quantity stimulation paste; Remanence; Yield improvement ration